Is There Really A Puzzle Over Negative Emotions And Aesthetic Pleasure? - León, María José Alcaraz (The Nordic Journal of Aesthetics, 2017)
Two seemingly contradictory aspects have marked art’s appreciation – and aesthetic appreciation in general. While an experience of pleasure seems to ground judgments of aesthetic value, some artworks seem to gain our praise by the very negative – unpleasant – experience they provoke. Known as the paradox of negative emotions, aestheticians have, at least since Aristotle, tried to deal with these cases and offer different explanations of the phenomenon. In this article, María José Alcaraz León does not directly offer an alternative explanation; rather she focuses on the apparent tension between an understanding of aesthetic experience in terms of a certain kind of pleasure and the negative aspect that is necessarily involved in our appreciation of painful art. The purpose of her article is to show that cases of artistic appreciation that involve negative emotions do not need to give up on the idea that aesthetic value is ultimately grounded upon an experience of pleasure.